Restoring bigcone Douglas-fir post-fire in drought-stricken Southern California: Assessing the effects of site choice and outplanting strategies - Runte, Gabriel C.; Oono, Ryoko; Molinari, Nicole A.; Proulx, Stephen R.; D’Antonio, Carla M. (Frontiers in Forests and Global Change, 2022)
Forest restoration is a powerful tool to combat the dual threats of drought and fire, both of which have been increasing in frequency and severity in recent years in the Western United States. The hard-hit region of Southern California is home to the endemic bigcone Douglas-fir, Pseudotsuga macrocarpa (Vasey), whose abundance and range have been impacted by multiple large fires within the last two decades. To better understand the ecology of these trees, and thereby improve the potential for restoration in light of predicted future conditions, we outplanted 1,728 seedlings into burned areas with varying levels of pre-planting fire severity and proximity to water (near canyon bottom and upslope). Within each planting area, seedlings were planted into one of four microhabitats; under conspecifics, under the codominant oak species (Quercus chrysolepis (Liebm)), in the open (no woody canopy), or in the open within a microsite feature such as a log, rock or a small shaded hole. At each site and within each microhabitat, half the seedlings were treated with oak-soil amendments (soil from under the oak) and half with spring watering (4 months after planting). To better understand the influence of outplanting conditions, we tracked the survival of the seedlings over the next two years. Short-term (March to June) survivorship following planting was quite high and the most significant die-off of seedlings occurred during the first dry season (June to November) despite strong droughts in the second and third dry seasons. Overall, only 7.3% (127 of 1,728) of seedlings survived. Seedling success depended strongly on the microhabitat and summer watering, though not in necessarily intuitive ways. Seedlings that received supplemental water during the first summer did worse than unwatered seedlings. The most successful microhabitats for planting were open sites with microsite features and sites underneath canyon live oak, while sites under mature bigcone Douglas-firs had the lowest rates of survival. Position on the slope had no effect on outcomes and soil amendment had a weak negative effect on seedling survival.